The Brazilian and the french private equity sectors from 2006 to present: a comparative analysis - Petit, Berengere Monique Ginette (2014)
Private equity, or the act of funds or investors to invest in companies unquoted on public exchange, has taken an increasing importance in the financial world in the past few years. Indeed, while the emergence of a private equity (PE) sector has been a major phenomenon in emerging markets since the middle of the 2000s, the worldwide financial crisis has weakened private equity in the developed world. Thus, this research will focus on two countries with supposedly very different dynamics regarding this sector: France and Brazil. The aim will be to discern general patterns of behavior in both PE sectors throughout a period running from 2006 to 2013, and try to determine to which extent they are comparable. Using the literature as the conceptual source for the comparative framework to be developed, it will be analyzed whether the market conditions and the institutional environment evolved during the studied period in both France and Brazil, if they compare, and if they impacted the level of private equity activity – supply and demand for funds – in both countries. To identify these patterns, this research will rely on an exploratory qualitative data analysis, based on a framework of the determinants of the PE sector identified and taken from the academic literature. This research will bring its contribution to the existing academic work on private equity thanks to its comparative nature and to its conclusion on the relevancy of the aforementioned determinants on private equity activity in France and Brazil.